Legal Protection of Victims of Verbal Catcalling in the Perspective of the Law on Criminal Acts of Sexual Violence - Sifa Aminudin; Yusuf Saefudin (Proceedings Series on Social Sciences & Humanities, 2023)
The purpose of this study is to evaluate the violence that often befalls women who are victims of verbal sexual harassment. Law Number 12 Year 2022 provides legal protection for victims of sexual violence (TPKS Law). The method used in this case study is the normative method. This is based on the fact that bullying is a form of verbal violence that expresses non-physical actions involving the body, sexual desire and inappropriate attractiveness to lower a person's mood. This can degrade human dignity based on their decency. As stipulated in the TPKS Law, victims of verbal sexual harassment have the right to be protected from actions that can degrade dignity. The form of protection is the implementation of duties and instilling a sense of security for victims, provided that it is carried out by LPSK and other institutions authorized by law. Verbal harassment or acts of violence should not be taken lightly, there must be firm action to provide a deterrent effect for the perpetrators. Because it is not only detrimental to the victim, but also a problem from the point of view of the norms that exist in society. In essence, humans are social creatures who live side by side to build community life and create synergy. Most catcalling occurs in community settings directed at women.